Interobserver reproducibility of radiographic evaluation of lumbar spine instability - Segundo,Saulo de Tarso de Sá Pereira (2016)
ABSTRACT Objective: To measure the interobserver reproducibility of the radiographic evaluation of lumbar spine instability. Methods: Measurements of the dynamic radiographs of the lumbar spine in lateral view were performed, evaluating the anterior translation and the angulation among the vertebral bodies. The tests were evaluated at workstations of the organization, through the Carestream Health Vue RIS (PACS), version 11.0.12.14 Inc. 2009© system. Results: Agreement in detecting cases of radiographic instability among the observers varied from 88.1 to 94.4%, and the agreement coefficients AC1 were all above 0.8, indicating excellent agreement. Conclusion: The interobserver analysis performed among orthopedic surgeons with different levels of training in dynamic radiographs of the spine obtained high reproducibility and agreement. However, some factors, such as the manual method of measurement and the presence of vertebral osteophytes, might have generated a few less accurate results in this comparative evaluation of measurements.